Population modification of malaria vector mosquitoes - James, Anthony A. (Henry Stewart Talks, 2018)
Synthetic genes added to mosquitoes suppress transmission of malaria parasites, Cas9-based gene drive for spreading supressive genes into mosquito populations, Gene driven strains and their role in sustaining malaria control and eradication, Novel regulatory and community engagement activities prior to field use of modified mosquitoes